(3ebOeI aj GdEOGQI h GdJMdjd GdeGdj (B/s - (3GdTfWj, Gjefs; (3GdMOQH, RgjQ s; (3YHO Gddg, YGeQ s ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2010)
(3eaGgje hhXGFa CgOGa GdGOGQI GdeGdjI , eUGOQ GdJehjd h GdYhGed GdeMOOI dGfhGY GdJehjd h GOGQI GdehLhOGJ , JMdjd GdJYGOd h JMdjd GdQaYY h cjajI GMJSGH GdaGFOI GdHSjWI h GdaGFOI GdeQcHI h GdbjeI GdMGdjI (B.s
(3eQGLY U(B.224s
Keywords: (3GdGOGQI GdeGdjIs; (3GdJMdjd GdeGdjs; (3GdJNWjW GdeGdjs